Some Observations on the applied becteriology of the avian salmonellosis - ΣΙΜΟΣ, ΕΥΑΓΓΕΛΟΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
During the period 1971 - 1973, 401 fowl specimens were examined bacteriologically. e. g. 93% from chicks and chickens and 7% from pigeons, canaries, pheasants e.t.c. Seventy five Salmonella strains were isolated (18,5%) and 47 were further serotyped (25 S. gallinarum, 9 S. pullorum, 12 S. typhi murium and 1 S. Saint-Paul). Observations concerning the media and the methodology used are given.